Celebrity and non-celebrity endorsement effectiveness on consumers' attitude towards advertisement - Wan Noraini, Wan Napi (2015)
Celebrity is frequently used in advertisement to build awareness towards the product and brand. It is referring to the percentage of people who are familiar with a particular product or brand being advertised. Traditionally awareness is built incrementally and a lot of money and time is spent. On the other hand, the time taken to build awareness is shorter if a celebrity is use in the advertisement. Celebrity is also being used to position a brand in order to make the brand more believable. However this study postulates that there is no difference using celebrity and non-celebrity toward consumer’s attitude on advertisement especially for the consumer goods. Thus the objective of this study is to investigate: (i) whether celebrity and non-celebrity have similar endorser impact on consumers’ attitude on advertisement and (ii) the effect of celebrity and non-celebrity endorser characteristics (attractiveness, trustworthiness, expertise and product - brand congruency) on consumers’ attitude on advertisement. The development of the questionnaire is based on the literature review. Using similar questionnaire but two different advertisement, celebrity and non-celebrity as the model, were distributed. Out of 400 questionnaires, 333 questionnaires were returned but only 325 questionnaires were usable. The descriptive, correlation and regression analysis were conducted. The results show that the relationship between the independent and dependent variables is positive. However the score for the advertisement using the celebrity as the model have a higher score compared to non-celebrity. Thus this study could be concluded that there is a difference in using celebrity toward consumers’ attitude on advertisement for consumer goods